1991
DOI: 10.1021/j100154a028
|View full text |Cite
|
Sign up to set email alerts
|

EXAFS determination of the structure of cobalt in carbon-supported cobalt and cobalt-molybdenum sulfide hydrodesulfurization catalysts

Abstract: The structure of the cobalt present in carbon-supported Co and Co-Mo sulfide catalysts was studied by means of X-ray absorption spectroscopy at the Co K-edge and by X-ray photoelectron spectroscopy (XPS). Thiophene hydrodesulfurization activities were used to measure the catalytic properties of these catalysts. By comparison of the EXAFS and XANES spectra of the catalysts with those of c 0 9 s S and Cos2 model compounds, it was concluded that all Co atoms in a catalyst prepared with nitrilotriacetic acid as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
85
2

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 209 publications
(108 citation statements)
references
References 4 publications
21
85
2
Order By: Relevance
“…Only, the Ni-Mo coordination number would have been expected to be equal to 1 to 2. We have indeed observed values of 1.4, 1.5 and 2.3 for N(Co-Mo) in the equivalent Co-MoS 2 structures supported on A120~, SiO 2 and C, respectively [10,13]. Why the M-Mo coordination number approaches 2 for the Co promoted catalysts, while it is about 1 for the Ni promoted catalyst, is not clear.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Only, the Ni-Mo coordination number would have been expected to be equal to 1 to 2. We have indeed observed values of 1.4, 1.5 and 2.3 for N(Co-Mo) in the equivalent Co-MoS 2 structures supported on A120~, SiO 2 and C, respectively [10,13]. Why the M-Mo coordination number approaches 2 for the Co promoted catalysts, while it is about 1 for the Ni promoted catalyst, is not clear.…”
Section: Discussionmentioning
confidence: 89%
“…The exact position of the Co or Ni atoms at the edges of the MoS 2 crystallites in the Co-Mo-S structure has still to be established, although informative EXAFS and XANES results have been published by Topsoe et al [6] and by Bouwens et al [7][8][9][10]. Since the beryllium windows of the in-situ EXAFS cell used in our investigations [7][8][9][10] contained a small amount of Ni, the Co EXAFS k-range which could be measured for Co-MoS 2 catalysts was somewhat limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most typical HDS catalysts consist of a MoS 2 active phase promoted by Co or Ni atoms, called 'CoMoS' or 'NiMoS' phase, both of which have been extensively researched [4][5][6][7][8][9], and by porous γ-Al 2 O 3 supports. Noble metals have often been proposed as newly developed active phases.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study using EXAFS (extended X-ray absorption fine Hydrodesulfurization of petroleum fractions such as structure) of the local structure of the Co _ Mo _ S phase diesel is becoming more and more important in the reported that cobalt atoms were coordinated to sulfur petroleum refining industry to satisfy environmental atoms in a square pyramidal structure similar to millerprotection requirements. Hydrodesulfurization procite 3) . A recent study investigated the NO adsorption esses have widely utilized cobalt (or nickel) promoted behavior and the magnetic properties of model Co _ Mo molybdenum catalysts for many years.…”
Section: Introductionmentioning
confidence: 99%